Terahertz refractive index control of 3D printing materials by UV exposure - Jang, Dahye; Lee, Sanggu; Ryu, Heonseong; Rho, Eui Young; Kim, Jeongmin; Seo, Minah; Lee, Tae Dong; Lee, Sang-Hun (Elsevier BV, 2025)
Recently, significant progress has been made in the development of THz optics based on metamaterials to overcome the limited availability of suitable materials for conventional optics. Although 3D printing technology is a promising method for rapidly fabricating these subwavelength structures, the structural degree of freedom for 3D printed metamaterials is still limited by the optical properties of printing materials. In this study, we controlled the THz refractive index and extinction coefficient of the 3D printing resin by UV exposure doses during the printing process. Samples were fabricated as uniform plates under different curing conditions in printing, and their optical properties were measured in the range between 0.3 THz and 2.0 THz using THz timedomain spectroscopy (THz-TDS). The refractive index and extinction coefficient were changed from 1.65 to 1.80, and from 0.04 to 0.12, respectively, with increasing UV doses from 1 mJ/cm(2), which allows resin to solidify and become printable, to 100 mJ/cm(2), where the optical changes become almost saturated. The results provide insights into optimizing the fabrication process of THz devices, even those with a gradient and complex refractive index profile, by utilizing 3D printing technology for a broad range of applications.